2021
DOI: 10.1186/s12883-021-02427-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal extensive transverse myelitis following ChAdOx1 nCOV-19 vaccine: a case report

Abstract: Background Transverse myelitis (TM) is a relatively uncommon condition, and vaccine-associated myelitis is even rarer. Concern regarding neurological complications following vaccination escalated following the report of TM during the safety and efficacy trials of the COVID-19 vaccine. Case presentation We report the first case of Longitudinal Extensive Transverse Myelitis (LETM) in Malaysia following administration of the chimpanzee adenovirus-vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…The longitudinally extensive TM (LETM) is a rare subtype of TM, in which the damage extends over 3 or more vertebrae (83). Reports regarding the LETM subtype started to emerge following the worldwide distribution of the COVID-19 vaccines (84)(85)(86)(87)(88). All cases occurred in patients under 60 years of age who presented with neurological symptoms starting within 3 weeks of receiving the first dose of the ChAdOx1 vaccine.…”
Section: Chadox1 (Astrazeneca) and Transverse Myelitismentioning
confidence: 99%
“…The longitudinally extensive TM (LETM) is a rare subtype of TM, in which the damage extends over 3 or more vertebrae (83). Reports regarding the LETM subtype started to emerge following the worldwide distribution of the COVID-19 vaccines (84)(85)(86)(87)(88). All cases occurred in patients under 60 years of age who presented with neurological symptoms starting within 3 weeks of receiving the first dose of the ChAdOx1 vaccine.…”
Section: Chadox1 (Astrazeneca) and Transverse Myelitismentioning
confidence: 99%
“…The PRISMA flowchart ( Figure 1 ) showed a search strategy for our review. The present study consisted of 28 studies, including 26 case reports, one case series, and one cross-sectional, and the pooled data of 31 patients with COVID-19 vaccine-associated ATM is extracted ( Sriwastava et al, 2021 , Sepahvand et al, 2022 , Tan et al, 2021 , Corrêa et al, 2021 , Vegezzi et al, 2021 , Hsiao et al, 2021 , Pagenkopf and Südmeyer, 2021 , Notghi et al, 2021 , Gao et al, 2021 , Malhotra et al, 2021 , Khan et al, 2022 , Erdem et al, 2021 , Hirose et al, 2021 , Tahir et al, 2021 , Miyaue et al, 2021 , Fujikawa et al, 2021 , Kaulen et al, 2022 , McLean and Trefts, 2021 , Alabkal et al, 2021 , Fitzsimmons and Nance, 2021 , Nakano et al, 2022 , Spataro et al, 2022 , Cabral et al, 2022 , Khan et al, 2022 , Maroufi et al, 2022 , Eom et al, 2022 , Netravathi et al, 2022 , Esechie et al, 2022 ). All of the selected studies were written in the English language.…”
Section: Resultsmentioning
confidence: 99%
“…Transverse myelitis is a rare phenomenon with an estimated incidence of between 1.34 and 4.6 cases per million annually. 8 ) Several TM cases reportedly occurred following administration of different vaccines, such as hepatitis B virus, human papillomavirus, seasonal influenza, measles-mumps-rubella, polio, and diphtheria, that occurred from a few days to 3 months after vaccination. 12 ) Currently, over ten cases of TM-associated COVID-19 vaccination have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular mimicry, epitope spreading, or polyclonal activation of B lymphocytes are possible mechanisms. 8 , 12 ) Bhat et al reported an association between TM and autoimmune diseases. 16 ) Our patient had no history of autoimmune diseases, but an anti-SSA antibody associated with Sjögren's syndrome was elevated.…”
Section: Discussionmentioning
confidence: 99%